ANTIMICROBIAL POTENTIALS OF ENDOPHYTIC FUNGI INHABITING RHODODENDRON ANTHOPOGON D. DON - Baral, Bikash; Rana, Prabina; Maharjan, Bijaya Laxmi (Ecoprint: An International Journal of Ecology, 2013)
Fungal endophytes have been studied from Rhododendron anthopogon D. Don Manaslu Conservation Area in Nepal. The endophytes were isolated from different parts of Rhododendron viz., root, stem and leaf using potato dextrose agar, malt extract agar and water agar. Altogether eighteen fungal endophytes belonging to nine genera were isolated. The endophytic species isolates belong to the genera Stemphylium, Alternaria, Penicillium, Aspergillus, Trichoderma, Papulaspora, Hansfordia, Wardomyces and Geotrichum. Out of 18 fungal isolates, 8 isolates could display antimicrobial activity inhibiting at least one of the test pathogens. Among the potent strains, 4 displayed both antibacterial and antifungal activities. Endophytic fungal isolates ERAA3, ERAA6 and ERAA8 displayed antimicrobial activity against all the tested bacterial (10) and fungal (5) pathogens. The endophytic strains were very effective against the bacterial pathogens and moderately active against the fungal pathogens. The study reinforced the assumption that endophytes of the high altitude medicinal plants could be a promising source of antimicrobial substances. DOI: http://dx.doi.org/10.3126/eco.v18i0.9397 Ecoprint: An International Journal of Ecology Vol. 18, 2011 Page: 39-44 Uploaded date: 12/20/2013